Effectiveness Of Pregnancy Class Implementation On Increasing Knowledge Of Delivery Preparation - Atalia Pili Mangngi; Brigita Dina Manek; Avelina Paskalia Gusman; Ermi Lilianda Alang; Devisarlina Babys; Maria Magdalena Theofila Duka (Lembaga Pengembangan Kinerja Dosen, 2025)
Pregnant Women Class is a place to learn for pregnant women about pregnancy health, childbirth, postpartum care, newborn care as well as myths and culture. Introduction All pregnancies are basically considered risky, During the course of pregnancy and childbirth, low-risk pregnant women can turn into high-risk, therefore continuous monitoring is needed during the pregnancy period and the birth process. The aim of this study was to determine the effectiveness of implementing classes for pregnant women in increasing knowledge in preparing for childbirth. Research method Quantitative research type True Experimental Design one group pretestposttest design. The research population is all pregnant women in Pukdale village Trimester two and Trimester three. Sampling with Proposive sampling using Simple Random Sampling. The research sample of 15 respondents was determined based on the inclusion criteria. The results of the study found that before being given education in the pregnant women's class, respondents had sufficient knowledge and after attending the pregnant women's class, respondents had good knowledge. Conclusion The results of the study prove that the Mother's Class is effective in increasing knowledge in preparation for childbirth, showing that the majority of respondents answered that it was effective, as many as 15 people (100%).